Analyzing the Impact of Foreign Investment on Trade Balance in Iraq: Evidence From 2005 to 2023 - Mohammed, Burhan Ali; Rostam, Biaban Nwri; Sharif, Nabard Abdallah (Journal of Economics and Administrative Sciences, 2025)
The paper investigates the impact of foreign investment on Iraq's trade balance between 2005 and 2023, particularly on exports and imports. Given the extreme reliance of the nation upon oil revenues and political-economic fluctuations, seasonal capital inflows are evaluated with respect to their influence on the trade dynamics of the country. Annual data and econometric methodological techniques, including stationary tests, cointegration analysis, Granger's causality test, and Vector Autoregressive (VAR) model, will be used to assess the long-run relationship between foreign investment and trade balance.Results show a significant and long-run relationship between foreign investment and Iraq's exports and imports. Foreign investment enhances export competitiveness and affects the patterns of imports. The channels of impact may differ across various states of the economy. The study calls for policy amendments to attract sustainable investment, improve business regulations, and lessen reliance on oil exports.The insights generated by the study shall be very useful for policymakers in charting a way to benefit foreign investment in the economic stability of the state. It stresses the need for economic diversification, improved investment laws, and infrastructure developments so as to maximize trade benefits. Future studies on Iraq should consider including important macroeconomic factors like GDP growth, exchange rates, and inflation to provide an integrated view of the economic future of Iraq.